Exploring the importance of discretionary mobility in later life. Issue 1 (13th March 2017) - Musselwhite, Charles
Abstract : Purpose: Travel and mobility for older people has typically focussed on the practical benefits to the individual, for example, in meeting utilitarian needs of shopping, appointments and staying connected to family and friends. However, previous research has hinted that travel for its own sake, to get out and about and feel and experience mobility, may be just as important for older people and is especially missed when individuals give-up driving. The paper aims to discuss these issues. Design/methodology/approach: This paper examines travel for its own sake, usually referred to as discretionary travel, interviewing 20 older people in each of three different contexts: for drivers, for community transport users and for non-drivers who receive lifts from family and friends. Findings: Older people not only enjoy discretionary travel, but also feel it is beneficial to their health and wellbeing. The car and especially driving, is seen as the best way to fulfil discretionary travel. Community transport users do fulfil discretionary travel needs but these are over formalised and lack spontaneity affecting feelings of control and identity. Receiving lifts from family and friends can often result in older people feeling a burden to the providers of the lifts especially when travel is viewed as discretionary. Practical implications: More needs to be done to ensure discretionary travel needs are met for those without cars, highlighting the importance of such travel to community transport providers and helping reduce the feeling of being a burden to family and friends. Originality/value: Policy, practice and research has tended to focus on transport as a means to an end. However, older people themselves value mobility just as much for its own sake and just to view nature. Such discretionary reasons for mobility are actually very important for health and wellbeing of older people and need more attention.